2018
DOI: 10.1016/j.toxrep.2018.08.017
|View full text |Cite|
|
Sign up to set email alerts
|

The use of structural alerts to avoid the toxicity of pharmaceuticals

Abstract: In order to identify compounds with potential toxicity problems, particular attention is paid to structural alerts, which are high chemical reactivity molecular fragments or fragments that can be transformed via bioactivation by human enzymes into fragments with high chemical reactivity. The concept has been introduced in order to reduce the likelihood that future candidate substances as pharmaceuticals will have undesirable toxic effects. A significant proportion (∼78–86%) of drugs characterized by residual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 31 publications
0
68
0
Order By: Relevance
“…In another study, structural features were used, which does not assure that relevant fingerprint as required for target selectivity (Alves et al, 2016). Use of molecular fragments does not assure about coverage of inter-fragment connection based substructures (Limban et al, 2018). Similarly there are other aspects which are not covered by ligand based comparative studied with set of compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, structural features were used, which does not assure that relevant fingerprint as required for target selectivity (Alves et al, 2016). Use of molecular fragments does not assure about coverage of inter-fragment connection based substructures (Limban et al, 2018). Similarly there are other aspects which are not covered by ligand based comparative studied with set of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, structural features based statistical QSAR models were defined structural alerts to flag potential chemical hazards (Alves et al, 2016). Molecular fragments with high chemical reactivity were also considered as structural alerts and were avoided to reduce toxicity in pharmaceuticals (Limban et al, 2018). Structure-metabolism studies are known to resolve reactive metabolite-related liabilities by "avoidance" strategies for exclusion of structural alerts and possible termination of reactive metabolite-positive compounds (Kalgutkar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Derivation of alerts by expert knowledge yields the advantage of an explanation for an alert. This explanation often results in mechanistic insights that subsequently can be used to suggest structural changes, where applicable . Independent of their source, structural alerts can help in the identification of hazards.…”
Section: Expert Methodsmentioning
confidence: 99%
“…It was also shown that the potency of an alert might be corresponding to the daily dose, therefore alerts might not be relevant for low doses of drugs . Alves and coworkers therefore proposed that structural alerts should not be seen as a ”yes” or ”no” concerning toxicity but rather as a hypothesis about the mode of action and subsequently trigger closer mechanistic studies . Similarly, Limban and coworkers propose the replacement of structural alerts by functional groups that counteract the supposed toxicity mechanism rather than directly rejecting such compounds .…”
Section: Expert Methodsmentioning
confidence: 99%
“…From the purely chemical side, we derived interpretable structural alerts related to DILI with the Molecular Substructure miner algorithm (MoSS) implementation of graph-based Molecular Fragment miner algorithm (MoFa) (24) and the fragment-based SARpy package (25), which could guide lead optimization to reduce the risk of DILI, as is currently standard practice for other toxicities (26). We then compared the quality of the derived structural alerts against the recent review of DILI related structural alerts by (27).…”
Section: Introductionmentioning
confidence: 99%